Non-smooth dynamics and multiple equilibria in a Cournot-Ramsey model with endogenous markups - Paulo Brito; Luís F. Costa; Huw Dixon (Cardiff University, Cardiff Business School, 2008)
We develop a simple Ramsey model with numerous Cournotian industries where entry generates an endogenous markup. The model produces two different regimes: a monopoly and an oligopoly one. We provide a rigorous study of non-smooth dynamics and we also analyse the global dynamics of the model, demonstrating the model exhibits robust heteroclinic orbits, either of the smooth or the non-smooth type. Similar economies may be in any of these regimes and they may change regime along its convergence path. Fixed costs and elasticities of demand, play a crucial role and changing their values may alter the dynamics in a radical way, either by inducing a discontinuous transition or a discontinuous hysteresis.
Keywords: C62; D43; E32; 330; endogenous mark-ups; non-smooth dynamics; discontinuous induced bifurcations; heteroclinic orbits; Gleichgewichtstheorie; Mark-up Pricing; Ramsey-Preis; Preiselastizität; Oligopol; Monopol